PENGEMBANGKAN BAHAN AJAR BERBASIS ETNOMATEMATIKA MENGGUNAKAN CANVA APPS PADA CANDI MUARO JAMBI UNTUK KELAS III SD - Ouralita, Silvi; Sastrawati, Eka; Budiono, Hendra (Universitas Bhinneka PGRI, 2024)
This research aims to describe procedures and describe the level of feasibility of developing ethnomathematics-based teaching materials using Canva apps at the Muaro Jambi temple for class III elementary schools. This research uses research and development (RD) methods using the ADDIE (Analysis, Design, Development, Implementation and Evaluation) model. From the research results, it is known that the ethnomathematics-based teaching materials using the Canva apps developed are very valid, having gone through the validity stages which were validated by 3 teams of experts. Among them, the validation results by material experts obtained an average score (4.5) in the very valid category. Media experts received an average score of (4.8) in the very valid category, and media experts received an average score of (4.8) in the very valid category. The results of the practicality of teaching materials from the teacher response questionnaire with an average score of 5 in the very practical category, and the results of the student response questionnaire with an average score of 5 in the very practical category. The conclusion of this research is that the development of ethnomathematics-based teaching materials using Canva apps at Muaro Jambi Temple for class III elementary schools is very feasible (very valid and very practical).